(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Drying cotton and cotton raw materials is an important step in their production, requiring significant energy consumption. This article discusses methods for improving energy efficiency in cotton drying. In particular, schemes and formulas are presented for optimizing the drying process using modern technologies and energy saving methods